Abnormal motor cortex excitability during linguistic tasks in adductor‐type spasmodic dysphonia. (8th July 2015) - Suppa, A.; Marsili, L.; Giovannelli, F.; Di Stasio, F.; Rocchi, L.; Upadhyay, N.; Ruoppolo, G.; Cincotta, M.; Berardelli, A.
Abstract In healthy subjects (HS), transcranial magnetic stimulation (TMS) applied during 'linguistic' tasks discloses excitability changes in the dominant hemisphere primary motor cortex (M1). We investigated 'linguistic' task‐related cortical excitability modulation in patients with adductor‐type spasmodic dysphonia (ASD), a speech‐related focal dystonia. We studied 10 ASD patients and 10 HS. Speech examination included voice cepstral analysis. We investigated the dominant/non‐dominant M1 excitability at baseline, during 'linguistic' (reading aloud/silent reading/producing simple phonation) and 'non‐linguistic' tasks (looking at non‐letter strings/producing oral movements). Motor evoked potentials (MEPs) were recorded from the contralateral hand muscles. We measured the cortical silent period (CSP) length and tested MEPs in HS and patients performing the 'linguistic' tasks with different voice intensities. We also examined MEPs in HS and ASD during hand‐related 'action‐verb' observation. Patients were studied under and not‐under botulinum neurotoxin‐type A (BoNT‐A). In HS, TMS over the dominant M1 elicited larger MEPs during 'reading aloud' than during the other 'linguistic'/'non‐linguistic' tasks. Conversely, in ASD, TMS over the dominant M1 elicited increased‐amplitude MEPs during 'reading aloud' and 'syllabic phonation' tasks. CSP length was shorter in ASD than in HS and remained unchanged in both groups performing 'linguistic'/'non‐linguistic' tasks. In HS and ASD, 'linguistic' task‐related excitability changes were present regardless of the different voice intensities. During hand‐related 'action‐verb' observation, MEPs decreased in HS, whereas in ASD they increased. In ASD, BoNT‐A improved speech, as demonstrated by cepstral analysis and restored the TMS abnormalities. ASD reflects dominant hemisphere excitability changes related to 'linguistic' tasks; BoNT‐A returns these excitability changes to normal.